Penyuluhan Germas (Gerakan Masyarakat) Hidup Sehat Bagi Anak-Anak RW 11 di Kelurahan Cawang Kota Jakarta Timur - Anita Sriwaty Pardede; Albert Hasibuan; I. Gusti Ngurah.Y.Usdayana; Halisa Kurniati; Fransiscus A.C.Wakumoan (Compromise Journal Community Proffesional Service Journal, 2025)
A healthy lifestyle needs to be instilled from an early age, one of which is through the habit of having breakfast that plays an essential role in maintaining health and supporting daily activities. Breakfast functions as the main source of energy after the body rests throughout the night, thereby influencing concentration, stamina, and productivity in both learning and working. However, in reality, many people, especially children, often skip breakfast due to various reasons such as limited time or lack of understanding about its benefits. Based on this condition, the community service team carried out a health promotion activity under the Gerakan Masyarakat Hidup Sehat (GERMAS) or Community Movement for a Healthy Life, with the theme “Let’s Have Breakfast Every Day” for children in RW 11, Cawang Sub-district, East Jakarta. This activity aimed to increase knowledge and awareness of the importance of breakfast as well as to build positive habits from an early age. The counseling was conducted through educational and interactive approaches so that children could understand the messages easily. It is expected that this activity will provide a real impact in changing the mindset of the community regarding the importance of breakfast, while at the same time supporting GERMAS in creating a healthy, productive, and high-quality generation.